Prevalence, genetic diversity and antiretroviral drugs resistance-associated mutations among untreated HIV-1-infected pregnant women in Gabon, central Africa - (:unkn) unknown (My University, 2012)
Background In Africa, the wide genetic diversity of HIV has resulted in emergence of new strains, rapid spread of this virus in sub-Saharan populations and therefore spread of the HIV epidemic throughout the continent. Methods To determine the prevalence of antibodies to HIV among a high-risk population in Gabon, 1098 and 2916 samples were collected from pregnant women in 2005 and 2008, respectively. HIV genotypes were evaluated in 107 HIV-1-positive samples to determine the circulating subtypes of strains and their resistance to antiretroviral drugs (ARVs). Results The seroprevalences were 6.3% in 2005 and 6.0% in 2008. The main subtype was recombinant CRF02_AG (46.7%), followed by the subtypes A (19.6%), G (10.3%), F (4.7%), H (1.9%) and D (0.9%) and the complex recombinants CRF06_cpx (1.9%) and CRF11_cpx (1.9%); 12.1% of subtypes could not be characterized. Analysis of ARVs resistance to the protease and reverse transcriptase coding regions showed mutations associated with extensive subtype polymorphism. In the present study, the HIV strains showed reduced susceptibility to ARVs (2.8%), particularly to protease inhibitors (1.9%) and nucleoside reverse transcriptase inhibitors (0.9%). Conclusions The evolving genetic diversity of HIV calls for continuous monitoring of its molecular epidemiology in Gabon and in other central African countries.
Keywords: African Research